Changing Pattern in Sweet Potato Cultivation in Semi-Arid Environment, Nigeria - J.O. Adejuwon; A.O. Olawole; N.O. Adeoye (Journal of Applied Sciences and Environmental Management)
Sweet potato, an herbaceous perennial vine is a sweet tasting tuberous root vegetable. Its importance lies on its sweetness and nutritional value. The varieties ranged from wild accessions to farmer varieties. In this study, thechanging pattern in sweet potato cultivation in the semi-arid environment in Nigeria is examined. Questionnaire was administered to 450 respondents from 15 agricultural settlements in 15 local governments in the study area, using clustered sampling technique. Data was analyzed using frequency counts, percentage and pairwise t-test. Results show twenty-seven varieties of sweet potatoes were cultivated in the basin, with 19 varieties planted in 1970’s and 24 varieties cultivated in 2000’s. Farmers no longer plant 3 varieties while 8 varieties were newly introduced. The farmers planting these varieties ranged from 0.2% to 20%. The planting of 7 varieties have reduced while there is an increase in the planting of 9 varieties. White sweet potato was the most popular and widely planted varieties, accounting for 18% and 20% in the 1970’s and 2000’s respectively. Factors that determine choice of the varieties planted include farmers’ choice of sweet potatoes is determined by nutritional value, skin colour, flesh colour, taste, size, personal preference, market value, demand, yield, appearance as well as resistance to pests and diseases. Farmers cultivating sweet potatoes in the basin have increased by 1.4% from 82.3% in 1970’s to 83.7% in 2000’s. Pairwise t-test showed that there is no significant difference in sweet potatoes varieties cultivated between 1970's and 2000's.